Case Report: Neurofilament light chain in the follow up of progressive multifocal leukoencephalopathy in a patient with multiple sclerosis treated with ocrelizumab - Piñar-Morales, Raquel; Calle-Calle, Raquel; Carrasco-Garcia, Maria; Davila-Arias, Cristina; Villar-Guimerans, Luisa Maria; Barrero Hernandez, Francisco J. (Frontiers in Pharmacology, 2025)
Progressive multifocal leukoencephalopathy (PML) results from the reactivation of John Cunningham virus JC virus and is a rare complication of anti-CD20 drug therapy. Neurofilament light chains increasingly serve as a marker of neuroaxonal damage in the follow-up of patients with multiple sclerosis (MS), but its role in the monitoring and detection of processes such as PML is yet to be defined. We report the case of a patient with MS who was treated with ocrelizumab and developed PML. Results: Serum neurofilament light chain (sNFL) levels were elevated at the diagnosis and progressively increased over his follow-up. Our results suggest that the monitoring of sNFL levels may be useful for the early diagnosis of PML in patients with MS.